Efficient recovery of high‐purity aniline from aqueous solutions using pervaporation‐fractional condensation system. Issue 12 (22nd August 2015) - Li, Chuncheng; Zhang, Xinru; Hao, Xiaogang; Wang, Minmin; Ding, Chuan; Wang, Zhongde; Wang, Yinan; Guan, Guoqing; Abudula, Abuliti
Abstract : Selective recovery of valuable minor component with high‐purity form from dilute aqueous solution is an interesting issue in the area of organophilic pervaporation. High‐purity aniline was recovered with a high production rate from dilute aqueous solution by a pervaporation‐fractional condensation (PVFC) coupling system. The effects of downstream pressure and temperature (the first condenser) on the performance of PVFC system were investigated based on experimental measurements and Aspen simulations. Sorption and desorption experiments demonstrated that the sorption selectivity of poly(ether block amide) (PEBA‐2533) membrane to aniline was extremely high, indicating excellent pervaporation performance for aniline/water solutions. The perfect integration of high‐performance PEBA‐2533 membrane with the fractional condensation process yielded high production rate of 1222.5 g/(m 2 h) as well as high recovery efficiency (86.5%) for recovering high‐purity aniline in the first condenser when feed concentration and temperature were 1 wt % and 80°C, respectively. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4445–4455, 2015